Age-related determinants of the walk-to-run transition in youth : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Sport and Exercise Science, Massey University, Wellington, New Zealand - Kung, Stacey Mikayla (Massey University, 2020)
There is a lack of consensus regarding when mature or adult-like gait is achieved in youth. The ability to adjust gait during the walk-to-run transition (WRT) may be a good indicator of whether gait has matured. Specifically, age-related differences in the preferred transition speed (PTS) and determinants of WRT can provide insight into self-organising behaviours and how effectively gait patterns are regulated in youth. This thesis therefore assessed WRT in 49 youth (10-17-year-olds) and 13 young adults (19-29-year-olds) to: 1) investigate how effectively youth can adjust to increasing gait speed; and 2) explore age-related differences in determinants of PTS. Participants completed a WRT treadmill protocol that started at a self-selected walking speed and increased by 0.06 m∙s⁻¹ every 30 s to determine PTS. Participants also walked and ran on a treadmill at speeds near PTS (PTS, PTS±0.14 m·s⁻¹, PTS±0.28 m·s⁻¹). During these tests, muscle activity (rectus femoris, biceps femoris, tibialis anterior, medial gastrocnemius), oxygen consumption, heart rate and perceived exertion were assessed for their role in determining PTS. There were no age-related differences in PTS despite there being anthropometric differences. However, 10-12-year-olds exhibited more exploratory behaviour when determining PTS, while adults and 15-17-year-olds generally used a single transition to determine PTS. Age-related differences in PTS determinants were observed. Specifically, the biceps femoris and medial gastrocnemius were additional weak links among 10-12-year-olds and 10-17-year-olds, respectively, suggesting these muscles continue developing through childhood and adolescence. Because youth transition to minimise the demands of more muscles than adults, they may have more conflicting sources of feedback arising from the musculature when adjusting their gait. The 10-14-year-olds also exhibited greater difficulties distinguishing differences in perceived exertion between walking and running at speeds near PTS. The inability to anticipate increases in effort as gait speed increased could explain the indecisiveness in determining PTS among 10-12-year-olds. Overall, this thesis improves our understanding about rate-limiting factors of gait maturation. It seems that 10-12-year-olds have more conflicting sensory cues involved in regulating gait, which can cause difficulties determining how to optimise their gait. As the musculoskeletal system matures through adolescence, so does the ability to adapt gait effectively.
Keywords: Gait in humans; Children; Youth; Physiology; Perceptual-motor processes; 420702 Exercise physiology